Studi Kelayakan Investasi Perumahan Menggunakan Metode Net Present Value (NPV) - Wulandari, Retno; Agustapraja, Hammam Rofiqi; Arif, Samsul (Jurnal Talenta Sipil, 2025)
Investment is the activity of allocating funds to assets or projects that aim to generate profits in the future. The housing sector is one of the attractive investment alternatives because its demand continues to increase. This study aims to assess the feasibility of investing in Sakura type houses at Chrysant Luxland Lamongan Housing project. The method used is investment feasibility analysis with the Net Present Value (NPV) approach. The data analyzed includes development costs, sales assumptions, and relevant interest rates. A descriptive quantitative approach was used in data processing. The results showed that the project generated an NPV value of Rp 221,248,788.21. This value reflects the positive added value of the investment made. Thus, the construction project of Sakura type houses is financially feasible. This investment is able to provide potential profits and a good return on capital. Based on these results, the Sakura type house in Chrysant Luxland Lamongan Housing can be used as a promising investment option, especially in the midst of the high community need for decent housing and continues to increase from time to time.